2021
DOI: 10.1108/ijoes-12-2020-0203
|View full text |Cite
|
Sign up to set email alerts
|

Social and ethical practices and firm value: the moderating effect of green innovation: evidence from international ESG data

Abstract: Purpose This study aims to examine the potential effect of integrating social and ethical practices into strategy on the market valuation of environmental, social and governance (ESG) businesses using the moderating effect of green innovation. Design/methodology/approach The sample used consisted of 523 international firms listed on the ESG index and headquartered in North America and Western Europe, forming an unbalanced panel of 7,845 observations spanning the period 2005–2019. The authors run a fixed-effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 95 publications
3
26
1
1
Order By: Relevance
“…Like previous works (Radhouane et al , 2018; Naeem et al , 2022; Verma et al , 2022), we opted for measuring financial performance by the market-to-book value (MTBV). This variable makes it possible to capture the reputational impact of environmental performance (Chouaibi and Chouaibi, 2021; Verma et al , 2022; Chen and Xie, 2022) and reflects the reaction of investors to the bank’s various environmental decisions (Lee et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Like previous works (Radhouane et al , 2018; Naeem et al , 2022; Verma et al , 2022), we opted for measuring financial performance by the market-to-book value (MTBV). This variable makes it possible to capture the reputational impact of environmental performance (Chouaibi and Chouaibi, 2021; Verma et al , 2022; Chen and Xie, 2022) and reflects the reaction of investors to the bank’s various environmental decisions (Lee et al , 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that using GI and environmental sustainability ideas, businesses could operate sustainably. Chouaibi and Chouaibi (2021) finding stated that societal and ethical strengths—combined with the moderating impact of GI—increase business value, whereas deficiencies do the opposite. Meanwhile, GI mediated the relationship between SP and lean production (Afum et al, 2021).…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In effect, previous research has demonstrated the importance of control variables in studies interested in the linkage between ESG and firm performance (Abdi et al , 2021; Chouaibi et al , 2021; Chouaibi and Chouaibi, 2021; Al Hawaj and Buallay, 2021). So, it is essential to include control variables such as firm growth or leverage, which is the ratio of debt to total assets (Mangalagiri and Bhasa, 2022; Mohammad and Wasiuzzaman, 2021; Abdi et al , 2021; García-Sánchez et al , 2021).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%